The novel from up above and the Anthropology from down below. Argueda’s foxes as experimental etnography - Benítez Leiva, Luciano (2011)
This article elaborates a reading of The Fox from up above and the Fox from down below by Jose Maria Arguedas, from an anthropological perspective, making it dialogue with the genre of experimental ethnography, framed within the positivist paradigm crisis in social sciences. This book aims to describe a complex intercultural context, developing a textual formula with higher powers than the indigenous novel approach or traditional ethnographic realism. While Arguedas has no scientific pretensions, his novel opens and reflects aspects of reality using resources such as collage, myth as historical background and polyphonic perspective through the discourse of social actors within the play. This makes evidence of his training as an ethnologist who is at once literary, enrolling in the phenomenon of blurred genders and the re-figuration of social thought (Geertz 1980). It starts from the novel in its entirety and the accompanying diaries, highlighting certain passages and nourishes of theoretical perspectives relating to ethnography, demonstrating the complexity of the arguedian style, such as theoretical and epistemological questions of anthropology in the second half of the twentieth century.